Assessment of the COBAS Amplicor HBV Monitor Test for Quantitation of Serum Hepatitis B Virus DNA Levels - Lopez, Vincent A. (American Society for Microbiology, 2002)
Treatment of patients with chronic hepatitis B virus (HBV) infections with potent antiviral therapy often results in dramatic reductions in the levels of viremia to very low levels. Monitoring of serum HBV DNA levels is a consistent method for the assessment of antiviral potency; however, widely used hybridization assays for the monitoring of HBV DNA levels have limited sensitivities and are not effective for the monitoring of patients whose serum HBV DNA levels have decreased to below approximately 700,000 HBV genomes/ml. The objective of the present study was to assess a PCR-based assay (the COBAS-AM assay) for quantitation of serum HBV DNA levels and to compare the results of the COBAS-AM assay with those of a solution hybridization assay with a radiolabeled probe. The precision and accuracy of the assay were determined with low-positive and high-positive controls consisting of a plasmid DNA molecule containing HBV-specific primer binding regions, and the sensitivity of the assay was determined by using serial dilutions of sera from subjects with chronic HBV infection. HBV DNA levels were quantitated in 1,695 serum samples from subjects with chronic HBV infection who were enrolled in clinical trials of lamivudine in North America or Asia. The COBAS-AM assay demonstrated high levels of inter- and intra-assay precision and accuracy, and the linear range of the COBAS-AM assay was greater than that of the solution hybridization assay. The assay is linear over a 3-log(10) range and is able to quantitate serum HBV DNA at levels 3 log(10) lower than those that can be detected by the solution hybridization assay. We found that the COBAS-AM assay is an accurate PCR-based assay for quantitation of serum HBV DNA levels in subjects with chronic HBV infection.